Transparency and Community Participation in Forest Resource Governance in Mt. Elgon Region, Kenya - Masaba, Protus Wanjala; Mbeche, Robert; Hitimana, Joseph (Journal of Forests, 2022)
The practice of good forest governance has been associated with reductions in poverty and community empowerment. This study assessed how the implementation of transparency and participation promote forestry practices under the plantation establishment for livelihood improvement scheme (PELIS) in the Mt. Elgon region. A sample size of 288 members of the Community Forest Associations (CFAs) and forest station managers drawn from three forest stations namely Saboti, Kimothon and Kaberwa were selected for the study. Focused group discussions and interviews administered through respondent assisted questionnaires were carried out to assess how the implementation of transparency and participation affect participants in PELIS. Local indicator variables were developed to assess transparency and participation. Chi-square tests of independence (α = 0.05) were performed to examine the relationship between the local indicator variables among sites based on the hypotheses that there were no significant differences in the implementation of transparency and participation among the sites. The study found statistical significance in accessibility to necessary information and decisions (p = 0.001) and involvement in decision-making processes (p = 0.002). Electoral related vices, conflicts and minimal women representation in executive committees undermines CFAs governance. The findings of this study indicates that CFAs governance systems directly affect forest conditions. The study generates information to support the formulation of policies and laws that can strengthen governance systems to minimize developmental deficits among CFAs and enhance socio-economic stability. Improved governance of CFAs will contribute in implementing agroforestry programmes that promote sustainable forest management in Kenya.